Comparing SeaDAS and ArcGIS Extracted Aqua MODIS Sea Surface Temperature DN Values at Bay of Bengal - , Jogiparthi Venkata Sai; , Kathavarayan Vasanth; , Madhavan Narayanan; , Thanabalan Palanisamy; , Veepanagandla Gnanendra; , Anaparthi Praneeth (Archives of Current Research International, 2025)
This study compares the Sea Surface Temperature (SST) DN values extracted from the Aqua MODIS data using SeaDAS and ArcGIS of Visakhapatnam coastal waters, Bay of Bengal (BOB), India. SST data from January to December 2024 were analyzed across buffer zones of 50 km ,75km,100km,125km,150km,200 km to assess their zonal statistics performance. Both tools showed high consistency, with absolute errors ranging from 0.000007°C to 0.000163°C and APE values ranging from 0.000023 to 0.000563. Errors were negligible up to 150 km, but a one-pixel discrepancy was observed at 200 km buffer, which slightly increased the error percentage. Seasonal pixel fluctuations, notably a 15-20% drop in July due to monsoon cloud cover, were observed. Both tools proved reliable for zone delineation, with negligible errors well below the ecological thresholds. SeaDAS excelled in precise SST processing, whereas ArcGIS offered superior geospatial visualization.